2020
DOI: 10.1186/s12866-020-01895-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the bacterial communities of psyllids associated with Rutaceae in Bhutan by high throughput sequencing

Abstract: Background: Several plant-pathogenic bacteria are transmitted by insect vector species that often also act as hosts. In this interface, these bacteria encounter plant endophytic, insect endosymbiotic and other microbes. Here, we used high throughput sequencing to examine the bacterial communities of five different psyllids associated with citrus and related plants of Rutaceae in Bhutan: Diaphorina citri, Diaphorina communis, Cornopsylla rotundiconis, Cacopsylla heterogena and an unidentified Cacopsylla sp. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 98 publications
(135 reference statements)
5
41
0
Order By: Relevance
“…Our study provides the most taxonomically and geographically diverse dataset of psyllid endosymbiont associations to date, covering 44 divergent taxa across five families. Our results suggest that psyllids house minimal bacterial communities, in agreement with more regionally focused studies of psyllid microbiomes and the microbiomes of other hemipterans (Thao et al, 2000a;Jing et al, 2014;Overholt et al, 2015;Morrow et al, 2017Morrow et al, , 2020Nakabachi et al, 2020a). Similar to the findings of Morrow et al (2017), we found that bacteria in the class Enterobacteriaceae are particularly prevalent in psyllid microbiomes (Figure 1 and Supplementary Table 5).…”
Section: Discussionsupporting
confidence: 88%
“…Our study provides the most taxonomically and geographically diverse dataset of psyllid endosymbiont associations to date, covering 44 divergent taxa across five families. Our results suggest that psyllids house minimal bacterial communities, in agreement with more regionally focused studies of psyllid microbiomes and the microbiomes of other hemipterans (Thao et al, 2000a;Jing et al, 2014;Overholt et al, 2015;Morrow et al, 2017Morrow et al, , 2020Nakabachi et al, 2020a). Similar to the findings of Morrow et al (2017), we found that bacteria in the class Enterobacteriaceae are particularly prevalent in psyllid microbiomes (Figure 1 and Supplementary Table 5).…”
Section: Discussionsupporting
confidence: 88%
“…For the family Psyllidae, only 26 Wolbachia strains are reported in PubMLST-Wolbachia (none of these belong to the genus Cacopsylla)-eight were isolated from Diaphorina citri and one was isolated from Heteropsylla sp., while for 17 isolated strains the host genus and the host species were not determined. Nevertheless, a number of studies dedicated to Cacopsylla associations with various bacterial endosymbionts [62,63], including Wolbachia [64,65], have been published over the past decade. It should be noted, that most of the published investigations contain data on a single (or very low number) of species, in which usually only a few individuals were tested.…”
Section: Wolbachia Infection In Hemipteramentioning
confidence: 99%
“…Put together, the exact biological nature and even the origin of the A-SBCA19 Buchnera are not clear and deserve further investigation. Based on 16S rRNA gene sequence, Morrow et al (2020) reported Buchnera in Diaphorina communis, as well as in other Cacopsylla species and Cornopsylla rotundiconis.…”
Section: Buchneramentioning
confidence: 99%